THE CONCEPT OF SIN IN SOCIETY (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
The article considers the concept of ―sin‖. The author justifies the thesis that ―sin‖ in its religious understanding gradually disappears from the vocabulary of a modern human being, it is replaced by the conception of ―diversity of human behavior‖. Identifying the nature and causality of sin, the author concludes that the human being is born with the rudiments of good and sinful inclinations, the manifestation of which depends on the atmosphere in the family, on the ideology of society. The concept of ―sin‖ determining moral guidelines requires updating considering changes in the society.